PENDEKATAN TaRL BERBANTUAN MEDIA AUGMENTED REALITY MENINGKATKAN LITERASI DAN NUMERASI SISWA SD NEGERI 2 MERAUKE - Tembang, Yonarlianto; Rahayu, Dewi Puji; Lieung, Karlina Wong; Hurit, Andreas Au; Sulistyowati, Retno Wuri; Mariyanto, Wiwin; Nurwidiyanto, Ali (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
The research aims to improve the literacy and numeracy of class II students at SD Negeri 2 Merauke in the odd semester of the academic year 2023/2024. This research is a classroom action research with full participation research and was carried out in two cycles consisting of planning, implementation, observation and reflection. The subjects of this research were 19 students of class 2. Data collection techniques were observation, documentation and interviews to determine student responses to the learning process. Based on the results of this research, it can be concluded that the implementation of the TaRL approach assisted by Augmented Reality (AR) media increased student literacy and numeracy in cycle I, student literacy was 47.37%, while for numeracy it was 42.11%. While in cycle II literacy and numeracy increased by 47.37%. 84.21% and in numeracy it was 78.95%. Based on this research, it can be concluded that using the TaRL approach assisted by Augmented Reality (AR) media can increase the literacy and numeracy of students at SD Negeri 2 Merauke.